Prediction of stroke or TIA in patients without atrial fibrillation using CHADS2 and CHA2DS2-VASc scores. Issue 19 (23rd May 2014) - Mitchell, L Brent; Southern, Danielle A; Galbraith, Diane; Ghali, William A; Knudtson, Merril; Wilton, Stephen B
Abstract : Objectives: To determine the accuracy of CHADS2 and CHA2 DS2 -VASc tools for predicting ischaemic stroke or transient ischaemic attack (TIA) and death in patients without a history of atrial fibrillation or flutter (AF). Methods: The study included 20 970 patients without known AF enrolled in the Alberta Provincial Project for Outcomes Assessment in Coronary Heart disease (APPROACH) prospective registry who were discharged after an acute coronary syndrome (ACS) between 2005 and 2011. The outcome measures were incident ischaemic stroke, TIA or death from any cause. Results: Over a median follow-up of 4.1 years, 453 patients (2.2%) had a stroke (n=297) or TIA (n=156) and 1903 (9.0%) died. The incidence of stroke or TIA increased with increases in each risk score (p<0.001), with an absolute annual incidence ≥1% with CHADS2 ≥3 or CHA2 DS2 -VASc ≥4. Both CHADS2 and CHA2 DS2 -VASc scores had acceptable discrimination performance (C-statistic=0.68 and 0.71, respectively). The mortality rate was also greater in patients with higher CHADS2 and CHA2 DS2 -VASc scores (p<0.0001). Conclusions: In patients with ACS but no AF, the CHADS2 and CHA2 DS2 -VASc scores predict ischaemic stroke/TIA events with similar accuracy to that observed in historical populations with non-valvular AF, but with lower absolute event rates. Further study of the utility of the CHADS2 and CHA2 DS2 -VASc scores for the assessment of thromboembolic risk and selection of antithrombotic therapy in patients without AF is warranted.